Quebra de paradigmas na contratação de serviços terceirizados – alcançar resultados através de contratos com foco em recursos humanos - Thaumaturgo da Silva, Eduardo Gonçalves; Arienti, Vinicius Leal (Revista Gestão da Produção Operações e Sistemas, 2007)
The evolution in the hiring of maintenance services has pointed out the performance-based model, or the availability- based model, as the most adequate one regarding outsourcing. The market has registered, year after year, the growth in the number of enterprises using such method. In many enterprises, there are pre-established conditions for the selection of applicants. In these situations, it is required certifications in the specific working areas, such as quality, environment, work safety and more recently, social responsibility. There are not many references concerning the collaborators of the hired enterprise and models that allow for the growth and the well-being of these workers. Due to the high level of commitment required in this model, the investment and follow-up of the involved human resources is necessary. Keywords: Contract, Outsourcing, Human resources